Pengembangan Literasi untuk Meningkatkan Minat Baca Siswa di SDN Gladak Anyar IV - Ria Kasanova (Departement of Mathematics Education, 2021)
The purpose of this study was to describe and analyze the development of the Literacy Culture of SDN Gladak Anyar IV Pamekasan students. This study uses a qualitative descriptive study method using a case study approach. Data collection methods were carried out through interviews, observation, and documentation obtained from school leaders, teachers, and students. Data analysis used an interactive model with data documentation, data visualization and validation. The process of developing a literacy culture is carried out in a three-step process. (1) Planning the development of a literacy culture, then setting goals, compiling programs, formulating strategies, and managing facilities and infrastructure. (2) Implementation of literacy culture development. The implementation of literacy culture development involves competency courses, development and training. (3) Assessment in the form of weekly, monthly and annual assessments. As a result, the results of the development of a literacy culture show that students' reading interest in reading can increase.